2023
DOI: 10.1108/tqm-08-2022-0248
|View full text |Cite
|
Sign up to set email alerts
|

Customer lifetime value: the effect of relational benefits, brand experiences, quality, satisfaction, trust and commitment in the fast-food restaurants

Abstract: PurposeThis study examines factors that affect customer lifetime value (CLV) in fast-food restaurants (FFRs) in Jordan. These factors are relational benefits, brand experiences, service quality (SQ), satisfaction, trust and commitment.Design/methodology/approachAn online survey was collected from a sample of 503 respondents. The authors used SPSS to test the constructs' relationships and analyse the data. SmartPLS was used to test the hypotheses.FindingsIn contrast to previous studies, not all dimensions of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Kim et al (2020) demonstrate a favorable and significant influence of sensory characteristics on consumer satisfaction. Dandis et al (2023) discovered no substantial association between sensory experience and customer satisfaction. Based on the explanation above, the next hypothesis proposed in this study is as follows: H4:…”
Section: Sensory Experiencementioning
confidence: 93%
See 2 more Smart Citations
“…Kim et al (2020) demonstrate a favorable and significant influence of sensory characteristics on consumer satisfaction. Dandis et al (2023) discovered no substantial association between sensory experience and customer satisfaction. Based on the explanation above, the next hypothesis proposed in this study is as follows: H4:…”
Section: Sensory Experiencementioning
confidence: 93%
“…Sensory provides for the visualization of intangible services and can aid in business promotion (Dandis et al, 2023). Han et al (2019) found that the brand experience at a coffeehouse had a considerable impact on customer satisfaction, with the sensory component having the highest coefficient value.…”
Section: Sensory Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…The influence of sensory and atmospheric experience on commitment has been established (Dandis et al, 2022;Schwaiger and Zehrer, 2022). These experiences can create a sense of commitment towards the mall.…”
Section: Ijrdm 522mentioning
confidence: 99%
“…The influence of sensory and atmospheric experience on commitment has been established (Dandis et al. , 2022; Schwaiger and Zehrer, 2022).…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%